Associations of Dietary Diversity and Other Factors with Prevalence of Stunting among Children Aged 6-35 Months - Kelvin Halim; Ratu Ayu Dewi Sartika; Trini Sudiarti; Primasti Nuryandari Putri; Nurul Dina Rahmawati (Indonesian Journal of Public Health Nutrition, 2020)
AbstractPrevalence of stunting among under five children in Indonesia is still considered as a public health problem. Dietary diversity, one of the important assessments in infant and child feeding practice, is one of important determinants of stunting. This study is aimed to examine associations between dietary diversity with other factors with prevalence of stunting in Babakan Madang District, Bogor Regency in 2019. A cross-sectional design study was performed in this study during April-June in 2019. A total of 149 children’s height aged 635 months was measured and defined based on WHO growth standards. Dietary diversity scores were collected from 24-hour food recall based on 7 food groups. Results showed that the prevalence of stunting in this study was 32.2% and 31.5% of them had low dietary diversity. There was association between dietary diversity and minimum acceptable diet with stunting (p-value = 0.033 and 0.013). Therefore, interventions should be taken by improving dietary diversity to reduce the burden and prevalence of stunting in both household and community level.AbstrakPrevalensi stunting pada balita di Indonesia masih merupakan masalah kesehatan masyarakat. Keragaman pola makan sebagai salah satu asesmen penting dalam praktik pemberian makan bayi dan anak, merupakan salah satu determinan penting untuk stunting. Penelitian ini bertujuan untuk mengetahui hubungan antara keragaman pola makan dan faktor lain terhadap prevalensi stunting di Kecamatan Babakan Madang Kabupaten Bogor tahun 2019. Studi cross sectional dilakukan pada penelitian ini selama bulan April -Juni tahun 2019. Sebanyak 149 anak usia 6-35 bulan diukur tinggi badannya dan didefinisikan menggunakan standar pertumbuhan tinggi badan menurut usia dari WHO. Skor keragaman pangan dikumpulkan dari Food Recall 24 jam berdasarkan 7 kelompok pangan. Hasil penelitian menunjukkan prevalensi stunting pada penelitian ini sebesar 32,2% dan sebanyak 31.5%-nya memiliki keragaman pola makan rendah. Terdapat hubungan antara keragaman diet dan asupan minimum yang dapat diterima dengan stunting (p value = 0.033 dan 0.013). Dengan demikian, intervensi harus dilakukan dengan meningkatkan k eragaman pangan untuk mengurangi beban dan prevalensi stunting baik di tingkat rumah tangga ma upun masyarakat.